2022
DOI: 10.3390/coatings12111688
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Effect of Eco-Friendly Silver Nanoparticles and Traditional Techniques on Aged Heritage Textile, Investigated by Dark-Field Microscopy

Abstract: An improper indoor microclimate has adverse effects on the state of preservation of historical textiles arranged in them, favoring the development of bacteriological microflora. The current study aims to combine traditional and innovative methods for cleaning and preserving a 100-year-old traditional blouse from Bihor, Romania. The material of the blouse was impregnated with 30 and 70 ppm silver nanosuspensions and washed with a substance obtained from boiling natural wood ash (lye). The research goals were to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 62 publications
(78 reference statements)
0
7
0
Order By: Relevance
“…Optimizing antibacterial properties and conductivity in wearable textiles requires a thorough understanding of the textile’s field performance. Historically, the integration of functional metals such as silver (Ag), reduced graphene oxide, titanium dioxide (TiO 2 ), and copper oxide (Cu 2 O) with textiles has been extensively employed to instill remarkable electrical conductivity and robust antibacterial characteristics. , Nevertheless, the integration of such metal-based materials might adversely affect the environment with the outcome of diminishing textile comfort. , …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Optimizing antibacterial properties and conductivity in wearable textiles requires a thorough understanding of the textile’s field performance. Historically, the integration of functional metals such as silver (Ag), reduced graphene oxide, titanium dioxide (TiO 2 ), and copper oxide (Cu 2 O) with textiles has been extensively employed to instill remarkable electrical conductivity and robust antibacterial characteristics. , Nevertheless, the integration of such metal-based materials might adversely affect the environment with the outcome of diminishing textile comfort. , …”
Section: Introductionmentioning
confidence: 99%
“…4,5 Nevertheless, the integration of such metal-based materials might adversely affect the environment with the outcome of diminishing textile comfort. 6,7 As a conducting polymer, polyaniline (PANI) offers an alternative due to its low toxicity, tunable electrical properties, biocompatibility, and ease of preparation. 8,9 In a recent review, protonated PANI textiles showed outstanding electrical conductivity and strong antibacterial properties against Gram-positive and Gram-negative bacteria.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, at present, there are many researches on the digital protection and innovative design of textile relics, but few researches on the washing treatment of textile relics, especially washing methods [1,10,11]. The selection of washing methods was the key to the washing work of textile relics, because the selection of washing methods directly determines the decontamination e ciency, the degree of preservation and damage of textile relics' original morphology [6,12,13]. At the same time, textile relics is extremely vulnerable, as a result of long-term exposure to decomposition of body, groundwater, soil, mineral microorganisms and other adverse environmental damage, suggesting the washing work of textile cultural relics had more challenge, should be especially cautious [2,14].…”
Section: Introductionmentioning
confidence: 99%
“…However, textile relics belong to the relics eroded by the corpse, coffin fluid, microorganisms, bronzes, wood, soil and other stains due to being long‐term buried in the ground (He et al, 2014; Li et al, 2021; Zhao, Pan, et al, 2019). Therefore, the surface or internal of textile relics are very easy to appear deposition of blood, protein, fat, adhesives, soil and rust and other pollutants (He et al, 2014; Ilies et al, 2022; Zhao, He, et al, 2019). Additionally, stains adsorbed on the surface or internal of textile relics cannot be removed in time, it not only reduces their ornamental value because of stain covering the unique texture, colors and patterns of textile relics, but also causes the physical chemistry or biological degradation of textile relics, and even carbonization or damage, eventually bug, losing its cultural, historical and artistic value (Ahmed & Ziddan, 2011; Ferrari et al, 2017; Kavkler et al, 2022).…”
Section: Introductionmentioning
confidence: 99%